Effectiveness of integrating technology across the curriculum: classroom learning environments among middle-school students in the USA - McDaniel, Donna Christine (Curtin University, 2015)
A pretest–posttest design was used in evaluating the effectiveness of integrating technology across the core curriculum in terms of students’ perceptions of their classroom learning environment for a sample of 966 grade 6–8 students in Texas. Data analyses supported the factorial validity and reliability of the Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) and revealed small and directionally-inconsistent changes in TROFLEI scale scores. Overall technology integration was neither advantageous nor disadvantageous.